SCIENTIFIC LIFE, SOL–GEL, 2016 (Proceedings of the YSU B: Chemical and Biological Sciences, 2016)
The 4th International Conference of CIS countries “Sol–Gel Synthesis and Investigation of Inorganic Compounds, Functional Hybrid Materials and Disperse Systems” (“Sol–Gel-2016”) by an initiative of the Institute of Silicate Chemistry of Russian Academy of Sciences (and the decision of the Organizing Committee of the previous Conference) will be held on September 19–23, 2016, in Yerevan.